2023
DOI: 10.1111/cas.15750
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic relevance of tumor‐resident memory T cells in metastatic lymph nodes of esophageal squamous cell carcinoma

Abstract: Tumor‐resident memory T (T RM ) cells in primary tumors are reportedly associated with a favorable prognosis in several malignancies. However, the behaviors and functions of T RM cells in regional lymph nodes (LNs) of esophageal cancer remain poorly understood. The aim of this study was to elucidate the effects of T RM cells in regional LNs of esophageal cancer on clinicopathological findings and prognosis. Specimens of esophageal cancer and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 36 publications
(83 reference statements)
0
10
0
Order By: Relevance
“…The preoperative regimens consisted of two cycles of 5-fluorouracil+cisplatin (FP), 5-fluorouracil+nedaplatin (FGP), or docetaxel+cisplatin+5-fluorouracil (DCF). The regimen schedules have been reported previously (7). FP consisted of a four-week cycle of 5-fluorouracil at 800 mg/m 2 body surface area on days one through five and cisplatin at 80 mg/m 2 on day one.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…The preoperative regimens consisted of two cycles of 5-fluorouracil+cisplatin (FP), 5-fluorouracil+nedaplatin (FGP), or docetaxel+cisplatin+5-fluorouracil (DCF). The regimen schedules have been reported previously (7). FP consisted of a four-week cycle of 5-fluorouracil at 800 mg/m 2 body surface area on days one through five and cisplatin at 80 mg/m 2 on day one.…”
Section: Methodsmentioning
confidence: 99%
“…Interestingly, we previously suggested that T RM in esophageal cancer is associated with the response to ICIs. Other studies have also reported that T RM has potential in the ICI treatment of gastrointestinal tumors (7,8). The evaluation of T RM is possibly instrumental, even for ICI treatment.…”
mentioning
confidence: 97%
See 2 more Smart Citations
“…CD103 is expressed by intraepithelial lymphocytes (αβ and γδ T cells), lamina propria T cells, regulatory T cells, and a subset of DCs. The presence of CD103 + resident memory T cells has been linked to better survival upon treatment in patients with head and neck squamous cell carcinoma [24] and esophageal cancer [42]. For example, Gattas G et al demonstrated that the presence of CD103 + CDS + tumor-infiltrating lymphocytes is associated with better responses to chemoimmunotherapy in patients with head and neck squamous cell carcinoma [43].…”
Section: Introductionmentioning
confidence: 99%